2019
DOI: 10.21083/partnership.v14i1.4743
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Customer Experience through Customer Journey Mapping and Service Blueprinting at Edmonton Public Library: An Exploratory Study

Abstract: This paper presents an overview of the design, implementation, and findings of an exploratory project to evaluate customer experience at Edmonton Public Library (EPL). The EPL Intern Librarian Project had three objectives: to establish the current state of customer experience at EPL, identify pain points, and develop recommendations for improvement. The study used the ethnographic methods of Customer Journey Mapping and Service Blueprinting to directly engage with customers and staff to produce visual document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Customer Journey Mapping (CJM) and Service Blueprinting were employed as realistic methods for measuring and enhancing the customer experience in a library context. Several suggestions were made to improve the user experience, such as increasing digital way finding, making catalog stations more visible, and revising website FAQs [37]. Moreover, the CJM is a tool for understanding the customer's decision-making process and experiences, which are key differentiators in the digital era.…”
Section: -2-customer Journey Mappingmentioning
confidence: 99%
“…Customer Journey Mapping (CJM) and Service Blueprinting were employed as realistic methods for measuring and enhancing the customer experience in a library context. Several suggestions were made to improve the user experience, such as increasing digital way finding, making catalog stations more visible, and revising website FAQs [37]. Moreover, the CJM is a tool for understanding the customer's decision-making process and experiences, which are key differentiators in the digital era.…”
Section: -2-customer Journey Mappingmentioning
confidence: 99%
“…The conducted analysis showed that there is a small number of studies relating to the identification of customer experiences in public organizations with the use of CJM. However, there is evidence of the positive effects of using this tool in the area of health care (Meyer, 2019, Borycki et al, 2020, in public libraries (Andrews and Eade, 2013;Mucz and Gareau-Brennan, 2019) and in government administration (Johnston and Kong, 2011;Bridge, 2012;D'Emidio et al, 2017).…”
Section: Customer Journey Mapping As a Tool For Identifying Customer Experiences In The Public Sectormentioning
confidence: 99%